Potensi Pendapatan Usaha Tani Karet dalam Pembiayaan Pendidikan Tinggi di Universitas Jambi - Yulia Putri Kartika; Kuswanto; Hidayatul Arief (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2025)
This study aims to determine the income potential of rubber farming in financing higher education at Jambi University. The research employs a descriptive quantitative approach, with data collection techniques including primary data and questionnaires distributed directly to rubber farmers. The sample consists of 51 farmers. The data analysis technique used is descriptive analysis, which aims to provide a detailed overview of the research object. This analysis includes calculations of the mean (M), median (Me), mode (Mo), and standard deviation (SD). Additionally, frequency distribution analysis is applied to identify data distribution patterns by grouping data into specific interval classes. The research findings indicate that the income potential (PP) of rubber farming is 1.07%, showing that PP > 1. Similarly, the income potential (PP) of non-rubber farming is 1.31%, also showing PP > 1. Therefore, the alternative hypothesis (Ha) is accepted, meaning that the income allocated for education is greater than the required costs.